A Review on Drug Delivery System for Tumor Therapy - Liu, Guoxiang; Yang, Lina; Chen, Guang; Xu, Fenghua; Yang, Fanghao; Yu, Huaxin; Li, Lingne; Dong, Xiaolei; Han, Jingjing; Cao, Can; Qi, Jingyu; Su, Junzhe; et al. (Frontiers in Pharmacology, 2021)
In recent years, with the development of nanomaterials, the research of drug delivery system has become a new field of cancer therapy. Compared with conventional anti-tumor drug, drug delivery systems such as drug nanoparticles (NPs) are expected to have more advantages in antineoplastic effects, including easy preparation, high efficiency, low toxicity, especially targeting ability. Drug delivery systems are usually composed of delivery carriers, anti-tumor drugs and even target molecules. At present, there are few comprehensive reports on summary of drug delivery system applied for tumor therapy. This review introduces the preparation, characteristics and applications of several common delivery carriers, and expounds the anti-tumor mechanism of different anti-tumor drugs in delivery carriers in detail which provide a theoretical basis for clinical application in the future.